Leadership in cyber security : who takes responsibility? - Balakrishnan, Kogila (2020)
COVID-19 has revealed vulnerabilities in many different sectors and amplified the risk of cyber security attacks. As humanity turns to digital platforms and connectivity, the cyber domain becomes increasingly critical but challenging. Who takes responsibility for providing leadership in cyber security?